Methicillin resistant Staphylococcus aureus (MRSA) nasal colonization: Could it be a professional restriction? - Santos, Cláudia (2021)
Objectives: Guideline research concerning screening and treatment of MRSA in asymptomatic patients.  Study design: Literature review.  Materials and methods: PubMed search was performed for: “nasal carriage MRSA”, “MRSA health care workers”, “community MRSA”, “MRSA control strategies”.  Results: The screening of colonization by MRSA and the application of decolonization measures in patients of health care units has an impact on decreasing the disease of this microorganism.  There are recommendations for health care professionals screening in order to reduce nosocomial transmission of MRSA, although its application in Portugal is still limited.  Conclusions: Currently, there is no formal indication for treatment of asymptomatic patients. When a professional has nasal colonization with MRSA the indication is to adopt preventive and contact protection measures. We propose a protocol for management of asymptomatic professionals with MRSA in nasal exudate.